THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND JOB MOTIVATION ON JOB PERFORMANCE TEACHERS OF UPPER SECONDARY SCHOOL AT JONGGGOL - Fariz Azhari; Bedjo Sujanto; Suryadi Suryadi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2020)
This aim of this research was to study the influence transformational leadership style and job motivation on job performance. The method used drwas a survey method with the type of explanatory research.The method used is this research was quantitative approach. Data survey collected 80 teacher. Data analysis using path analysis. Based on hypothesis testing that has been done, it can be described as the following research findings: (1) there is a positive direct influence of transformational leadership style on job performance, (2) there is a positive direct influence of job motivation on job performance, (3) there is a positive direct influence between transformational leadership style on job motivation.